PERLINDUNGAN HUKUM HAK ATAS KEPASTIAN KERJA TERHADAP REGULASI JANGKA WAKTU PERJANJIAN KERJA WAKTU TERTENTU (PKWT) PASCAUNDANG-UNDANG CIPTA KERJA - Roah Perliawati; Mohammad Perdana Diputra; Ricky Maulana; Ipah Atipah; Agus Septima Ridwan (JOURNAL OF LAW AND NATION, 2026)
This research examines the juridical implications of extending the maximum duration of Fixed-Term Employment Agreements (PKWT) to five years under Article 6 of Government Regulation Number 35 of 2021 as a derivative of the Job Creation Law, with respect to workers' right to job security in Indonesia. Two research problems are addressed: first, what are the juridical implications of the change in PKWT duration from the perspective of job security principles; and second, what legal protections remain available for contract workers after the enactment of the Job Creation Law. This research employs normative juridical methods with statutory and conceptual approaches and analyzes legal materials descriptively and qualitatively. The findings reveal that the elimination of renewal frequency limitations and the extension of the contract tolerance period to five years systematically degrades workers' right to job security. The new regulation creates legal loopholes for employers to misuse the right to fill permanent positions with repeatedly extended contract workers without any obligation to regularize their employment status, resulting in the juridical protection of the state toward contract workers declining to its most minimal point.